2004
DOI: 10.1039/b404047c
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of Ni(ii) and Co(ii) ions on the sulfite induced autoxidation of Cu(ii)/tetraglycine complex

Abstract: The synergistic effect of Ni(II) and Co(II) on the sulfite induced autoxidation of Cu(II)/tetraglycine was investigated spectrophotometrically at 25.0 degrees C, pH = 9.0, 1 x 10(-5) mol dm(-3) < or = [S(IV)] < or = 8 x 10(-5) mol dm(-3), [Cu(II)]= 1 x 10(-3) mol dm(-3), 1 x 10(-6) mol dm(-3) < or = [Ni(II)] or [Co(II)] < or = 1 x 10(-4) mol dm(-3), [O2] approximately 2.5 x 10(-4) mol dm(-3), and 0.1 mol dm(-3) ionic strength. In the absence of added nickel(II) or cobalt(II), the kinetic traces of Cu(III)G4 fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 25 publications
3
41
0
Order By: Relevance
“…Our previous studies with tetraglycine as a ligand showed that the Cu(III)/G 4 formation is a linear function with initial sulfite concentration and can be monitored amperometric 22 and spectrophotometically 1,8,23 at 365 nm. For analytical purposes S(IV) could be determined in wine and juices in the range of (0.5-10) × 10 -5 mol L -1 and detection limit 6.0 × 10 -7 mol L -1 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Our previous studies with tetraglycine as a ligand showed that the Cu(III)/G 4 formation is a linear function with initial sulfite concentration and can be monitored amperometric 22 and spectrophotometically 1,8,23 at 365 nm. For analytical purposes S(IV) could be determined in wine and juices in the range of (0.5-10) × 10 -5 mol L -1 and detection limit 6.0 × 10 -7 mol L -1 .…”
Section: Resultsmentioning
confidence: 99%
“…However great advances were achieved in some cases, in the presence of complexing medium, where it was possible to follow the formation of one of the metal ion, at trivalent state in large excess (10 -4 -10 -3 mol L -1 ), and the effect of the presence of the second metal ion at very low concentrations (10 -8 -10 -5 mol L -1 ). [2][3][4][5][6][7][8][9] Previous work reported in the literature [1][2][3][4][5][6][7][8][9][10] carried out in complexing medium, using very low concentrations of S(IV) (10 -5 mol L -1 ) and the second metal ion (10 -8 -10 -5 mol L -1 ) showed the complexity of the systems.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22] The literature reports only few studies on DNA damage mediated by Cu(II) (added as a free ion or complex) in the presence of S(IV) and dissolved oxygen. [19][20][21][22][23][24] Previously, we showed that the oxidation of S(IV) in air saturated solution ( 13,14,16,17 In addition, we verified that Cu II G 4 complexes interact with DNA producing strand breaks in significant yields in the presence of S(IV) without or with a second metal ion (traces of Ni(II)). 22 …”
Section: Introductionmentioning
confidence: 90%